Practicing ministry in the presence of God : theological reflections on ministry and the Christian life - Davis, John Jefferson (Eugene, OR Cascade Books, 2015)
Practicing Ministry in the Presence of God presents a new paradigm for church ministry--one that is based on fundamental truths of the Christian faith such as the Trinity, union with Christ, and the already presence of the Holy Spirit in the church. This new paradigm can help busy pastors avoid burnout in the ministry and model Trinitarian, New Testament patterns of ministry to their people. Practicing Ministry in the Presence of God reflects the best of recent New Testament scholarship, sensitivity to the contexts of globalized postmodern cultures dominated by digital media, and practical applications for Christian life, discipleship, worship, and mission.
Includes bibliographical references (pages 291-320).
Keywords: Theology, Practical; Pastoral theology; Christianity and culture; Christianity and culture; Pastoral theology; Theology, Practical